Efektifitas Penggunaan Kahoott Sebagai Media Evaluasi Hasil Belajar Bahasa Arab Kelas Satu Madrasah Aliyah Matholi’ul Anwar Simo Sungelebak Karanggeneng Lamongan - Aniisa'atus Salamiyah; M Rizal Rizqi; Nisaul Barokati Seliwo Wangi (AJER: Advanced Journal of Education and Religion, 2025)
This research is based on the lack of innovation of teachers in using social media as a medium for evaluating Arabic subjects. The purpose of this writing is to find out the Effectiveness of the Use of Kahoot as a Media for the Evaluation of Arabic Learning Outcomes for First Class Madrasah Aliyah Matholi'ul Anwar Simo Sungelebak Karanggeneng Lamongan. In this study, the researcher uses a quantitative method The research design used in this study is a pre-experiment design in the form of a one shot case study. The data collection method uses test techniques, observations, questionnaires and documentation. The result of this research is that students admitted that it is easier to understand maharoh istima' and maharoh qiroah with Kahoot media because the material listened to tends to use the original voice of eastern people. And some students feel enjoyed and challenged when evaluating with kahoot and some do not because each question has a time limit so that students feel rushed when answering questions. Evaluation with Kahoot media can increase student motivation due to the many features that Kahoot has, students can also find out the value of each time they finish answering questions. The average score of learning outcomes obtained by students was 77.2 out of 25 students and students who achieved learning completeness were as many as 23 people with a percentage of 92%, so it can be said to be classically complete because more than 75% of students achieved the KTTP score of the Independent curriculum. The average percentage of student responses was 100% and was classified as a very good (positive) response to the evaluation of Arabic language learning with kahoot media.